Analisis Peningkatan Kualitas Permukiman Kumuh di Desa Loh Sumber Kabupaten Kutai Kartanegara - Lisa Astria Milasari; Faizal Baharuddin; Rusdi Doviyanto (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
Population growth is a high primary need, one of which is the need for housing. The existence of slum settlements in the Kutai Kartanegara Regency has an indication of social and environmental problems. From the results of the location justification that the densest slum area is in Loh Sumber Village in RT. 02 and RT. 03 with a land area of ​​5.31 hectares. This study aims to provide input through the concept of improving the quality of slum settlements, with the research approach used is a rationalistic approach, based on truth. The research method is in the form of a qualitative descriptive study, with the answer to an ongoing problem. The research indicators and variables are (1) the physical condition of the building, with the variables of building density and building quality; and (2) The condition of facilities and infrastructure, with variables of road environmental quality, environmental drainage, quality of drinking water network, solid waste management, quality of wastewater and sanitation, and public street lighting. The results of the discussion are the concept of rejuvenation in the form of the use of building roof materials, and the use of wood types as building materials with strong resistance to air, repair of environmental roads with concrete and paving blocks, by changing the direction of the directions. as a street name marker, improve the quality and quantity of the system. clean water, manufacture of wastewater from IPAL / IPLT, determine the location of TPS, and public street lighting. The need for local government cooperation in implementing community needs and involving the active role of the community in maintaining a clean and safe residential environment.